Development of a Project-Based e-Portfolio for Enhancing Critical and Creative Thinking Skills in Land Pollution and Waste Management Education - Yuliaturosida, Eka; Suyono, Suyono; Tukiran, Tukiran; Satriawan, Muhammad (FKIP Universitas Lampung, 2025)
Critical and creative thinking skills are the core of 21st century skills that learners must have to face global challenges. The ability to interpret, analyze, evaluate, inference, explanation, self regulation, think fluency, flexibility, originality and elaboration can shows the level of their critical and creative thinking ability. The research aims to develop e-portofolio for enchancing the critical and creative thinking ability of 8th level students at Junior High School by soil pollution and waste management education. The research used a one-group pretest-posttest experimental design. The validity of e-portfolios consists of construct and content validity. The practicality of e-portfolios was assessed based on student response questionnaires. The effectiveness of the e-portfolio was assessed through a test designed to measure their critical and creative thinking skills. After the e-portfolio trial, a test was conducted to enable the improvement of critical and creative thinking skills. This study used the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) which is limited to three stages namely analysis, product design and development. The validity assessment used expert judgement. The design of e-portfolio learning media involves elements that are in accordance with the indicators of critical and creative thinking by providing feedback, self-assessment, peer assessment, self-reflection. The data generated in this study is the validity of e-portfolios to measure critical and creative thinking skills. Based on the profile analysis of critical and creative thinking skills of SMP Negeri 8 Purwosari students, it was found that there was an increase in the percentage of critical thinking skills of grade VIII students from 73.08% in the very low category (19 students) to 88.46% in the very high category (21 students). It was also found that the percentage of creative thinking ability of the largest VIII grade students was 69.23% in the very low category (18 students) to 46.15% in the very high category (12 students) after using e-portfolios. This research developed e-portfolios as an innovative instrument that not only measures critical or creative thinking ability separately, but also learns both critical and creative thinking ability . In its implementation, the e-portfolio is designed to integrate various learning components, such as problem-based assignments, case studies, experiments and self-reflection that are relevant to practising critical and creative thinking skills. Keywords: critical thinking ability, creative thinking ability, e-portfolio, pancasila student profile.